Potential impact of the EVLA on studies potential impact of the EVLA on studies of thermal radio emission from cool evolved K and M star winds - HARPER, GRAHAM (ASP, 2008)
Cm-radio observations of evolved K and M stars made at the VLA and ATCA, and subsequent detailed atmospheric modeling, have revealed that the thermal emission originates from the wind acceleration region close to the star. The temperature and density gradients can only be coarsely described for the handful of stars with existing two or three wavelength detections. The EVLA will provide an order of magnitude increase in sensitivity over the VLA, coming mainly from the increase in available correlator band-width, and this will oer the opportunity to map the density and temperature structure of the stellar winds with unprecedented clarity. We present new radio uxes for cool evolved stars ( TrA K3 II, Gru M5 III) and use these and existing data to examine the role that the EVLA will play in future wind studies.
PUBLISHED
Keywords: Physics